Energy Technology 2017 : Carbon Dioxide Management and Other Technologies - Zhang, Lei; Drelich, Jaroslaw W.; Neelameggham, Neale R.; Guillen, Donna Post; Haque, Nawshad; Zhu, Jingxi; Sun, Ziqi; Wang, Tao; Howarter, John A.; Tesfaye, Fiseha; Ikhmayies, Shadia; Olivetti, Elsa; et al. (The Minerals, Metals & Materials Series,, 2017)
This collection focuses on energy efficient technologies including innovative ore beneficiation, smelting technologies, recycling and waste heat recovery. The volume also covers various technological aspects of sustainable energy ecosystems, processes that improve energy efficiency, reduce thermal emissions, and reduce carbon dioxide and other greenhouse emissions. Papers addressing renewable energy resources for metals and materials production, waste heat recovery and other industrial energy efficient technologies, new concepts or devices for energy generation and conversion, energy efficiency improvement in process engineering, sustainability and life cycle assessment of energy systems, as well as the thermodynamics and modeling for sustainable metallurgical processes are included. This volume also offers topics on CO2 sequestration and reduction in greenhouse gas emissions from process engineering, sustainable technologies in extractive metallurgy, as well as the materials processing and manufacturing industries with reduced energy consumption and CO2 emission. Contributions from all areas of non-nuclear and non-traditional energy sources, such as solar, wind, and biomass are also included in this volume. Papers from the following symposia are presented in the book: Energy Technologies Advances in Environmental Technologies: Recycling and Sustainability Joint Session Deriving Value from Challenging Waste Materials: Recycling and Sustainability Joint Session Solar Cell Silicon.